Role of pregnancy associated plasma protein-A and doppler velocimetry in the assessment of fetomaternal outcome in high risk pregnancy - Kaundal, Asmita; Gupta, Usha; Bhattcharjee, Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The study aimed at defining the role of Pregnancy associated plasma protein-A (PAPP-A) and uterine artery doppler (Ut.A.PI) in the development of adverse pregnancy outcome (APO) in high risk pregnancies. Methods: This was an observational study where 100 singleton pregnancies at high risk of development of APO, between 11 to 13 + 6 weeks POG were enrolled. PAPP-A levels were measured at 11 to 13 + 6 weeks POG and uterine artery doppler PI was measured at 20 weeks. Women were followed till delivery. Pregnancy outcome were seen and a cut off at which APO developed was derived. Results: In this study women with lower mean PAPP-A (0.75±0.19 MOM versus 1.23±0.31MOM) (p<0.001) values and higher Ut.A.PI (1.43±0.35MOM versus 0.99±0.25MOM) (p<0.001) developed APO. Cut off value for PAPP-A and Ut.A.PI was determined and was found to be ≤11.65 µg/ml (≤0.79MoM) and >1.42 (>1.19MoM) respectively which was higher than what is determined in other studies done on low risks populations thereby suggesting for an intervention or more meticulous observations at a higher cut offs. Conclusions: PAPP-A and uterine artery doppler are already being used for the screening of preeclampsia in most of the countries but not for other adverse pregnancy outcomes. PAPP-A levels along with the uterine artery PI in predicting APO in high risk women has high negative predictive value. Hence can be uses as a screening method in high risk population whether they should be used for low risk population also needs further evaluation.